Two new species of the genus Candida in the Zygoascus clade, Candida lundiana sp. nov. and Candida suthepensis sp. nov., isolated from raw honey in Thailand - Saksinchai S. (2014)
During a survey of yeasts associated with raw honey collected in Thailand, two strains of the Zygoascus clade were isolated from the Asian cavity-nesting honeybee Apis cerana and the stingless bee Homotrigona fimbriata. Phylogeny based on 26S rDNA D1/D2 sequences placed these yeasts as members of a clade including Candida bituminiphila, Candida patagonica and Candida polysorbophila. The strains of the two novel species, CBS 12271 T and CBS 12270 T, respectively, could be unquestionably distinguished from their relatives by rDNA sequences and other taxonomic characteristics. Therefore, the novel anamorphic species, Candida lundiana sp. nov. (type strain CBS 12271 T = JCM 16823 T) and Candida suthepensis sp. nov. (type strain CBS 12270 T = JCM 16822 T) are described. © 2011 Springer Science+Business Media B.V.